Petrography of El Baúl massifgranitoids, Cojedes state, Venezuela - Viscarret, Patxo; Urbani, Franco (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
The granites El Mogote, Mata Oscura and Piñero outcrop in the El Baúl massif, next to metasedimentary, volcanic and Â Â sub volcanic rocks, to the south of Cojedes state, Venezuela. El Mogote Â Granite, is sintectonic respect to the Taconic orogenesis (Caledonian) and is the most representative of the massif. The lower Permiangranitoids are controlled by the Apalachian event (Hercinian or equivalent) and are post-orogeny to this event. El Mogote Granite was emplaced at shallow crustal and represents a magmatic event-granite of the Early Paleozoic. The Mata Oscura and Piñero granites, were emplaced in middle and higher crustal levels, respectively, together with the Volcanic of Guacamayas. The aplitic dykes of this last event cut metasedimentary Â Â units and granite. El Mogote Granite is characterized by presenting porphydic seudo rapakivi texture with alkalifeldspar.The Mata Oscura Granite are of medium to coarse grain and The Piñero Granite have fine grain and present myrmekite, micrographic, symplectite, grano phydicandperthite textures. The diferente textures and mineralogical compositions described in this work have provided novel geological subunits contributing new petrological information on the evolution of El Baúl massif.Â